Asset price bubbles : implications for monetary and regulatory policies - Kaufman, George G.; Western Economic Association; European Financial Management Association (Amsterdam ; New York : JAI, 2001)
A study of asset price bubbles and the implications for preventing financial instability. This book examines asset price bubbles to further our understanding of the causes and implications of financial instability, focusing on the potential of central banks and regulatory agencies to prevent it. The book grew out of a conference jointly sponsored by the Federal Reserve Bank of Chicago and the World Bank Group in April 2002.
The papers in this volume were presented at special sessions at the annual meetings of the Western Economic Association in San Francico in July 2001 and of the European Financial Management Association in Lugano, Switzerland in June 2001"--Page ix.
Includes bibliographical references.
oif 31/08/15
Loan
Keywords: Financial crises -- Congresses; Financial services industry -- Congresses; Monetary policy -- Congresses; Deposit insurance -- Economic aspects -- Europe -- Congresses; Real property -- Economic aspects -- Asia -- Congresses; Stock exchanges -- United States -- Management -- Congresses